Perancangan Model Otomasi pada Industri Furnitur di Jepara Studi Kasus Produk Wood Cap - Husain, Fakhril; Djorgie, Thomas; Herliansyah, Muhammad Kusumawan; Sari, Wangi Pandan (Institut Teknologi Dirgantara Adisutjipto, 2024)
The furniture industry in Jepara Regency, Central Java, is renowned for exporting high-quality products. One such product is the wood cap, which is used to cover the top of fences. The current manual production of wood caps results in a slow process. This research proposes an automation system to enhance efficiency, transforming the production process into two stages using an inclined plane, pushers, and a conveyor. This system integrates a block diagram, logic gates, a ladder diagram, and control devices, including limit switches, pressure switches, and an emergency button. The implementation of this automation allows orders to be completed in 50 days, significantly faster than the 150 days required by the manual system.